Genetic control of scald resistance in barley landraces - O. N. Soboleva; G. S. Konovalova; E. E. Radchenko (Вавиловский журнал генетики и селекции, 2016)
Scald (Rhynchosporium secalis (Oudem.) J.J. Davis pathogenic agent) is one of the most harmful barley diseases. A high variability of this fungi explains the occurrence of new aggressive pathotypes and, accordingly, loss of cultivar resistance. It was found that many recently selected varieties of barley and previously identified sources of resistance to R. secalis are now susceptible to the pathogen. There is only one gene, Rrs9, that maintains efficiency against pathogen populations in Russia. The aim of this study is to find donors of genes for effective resistance to scald with the ability to easily transfer this trait for hybridization. The inheritance of scald resistance in 33 barley landraces was studied. Analysis of the interaction between the pathogen test clones and the host plant revealed a difference between the alleles determining fungal resistance in 32 barley forms, the previously effective genes Rrs4, rrs6, rrs7, and currently effective Rrs9. It was found that 30 accessions are protected by new unidentified genes for scald resistance. Accessions k-18398 and k-16231 from China are likely to possess allelic genes for scald resistance, while the gene (or genes) of accession k-31075 from Nepal is allelic to the Rrs9 gene. It was demonstrated by hybridological analysis that accessions k-3307, k-15868, k-18989 and k-3481 are protected by effective genes for scald resistance, which differ from each other and which are not allelic to the Rrs4, rrs6, rrs7 or Rrs9 genes. Accessions k-15868 and k-3481 possess two complementary recessive genes for scald resistance, k-18989 has two recessive genes, and k-3307 carries one recessive gene for pathogen resistance. The resistance genes of these forms are manifested during all the stages of plant ontogenesis.